2016
DOI: 10.1074/jbc.m115.678235
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic and Antiresorptive Modulation of Bone Homeostasis by the Epigenetic Modulator Sulforaphane, a Naturally Occurring Isothiocyanate

Abstract: Bone degenerative pathologies like osteoporosis may be initiated by age-related shifts in anabolic and catabolic responses that control bone homeostasis. Here we show that sulforaphane (SFN), a naturally occurring isothiocyanate, promotes osteoblast differentiation by epigenetic mechanisms. SFN enhances active DNA demethylation via Tet1 and Tet2 and promotes preosteoblast differentiation by enhancing extracellular matrix mineralization and the expression of osteoblastic markers (Runx2, Col1a1, Bglap2, Sp7, Atf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 69 publications
6
60
0
Order By: Relevance
“…Consistent with its functional role in bone cell differentiation, Suv420h2 depletion by siRNA suppresses the maturation potential of MC3T3-E1 pre-osteoblastic cells by reducing Alp activity, ECM mineralization, as well as the expression of osteoblast-related biomarkers (e.g., Ibsp , Col1a1 or Sp7 ). Our finding that Suv420h2 is a positive regulator of osteoblast differentiation complements our previous studies that established the importance of other epigenetic regulators, including the H3K27 methyl transferase EZH2 (4, 5), DNA hydroxymethylases TET1 and TET2 (2, 3), DNA methyl-transferases (29, 30) and histone deacetylases (31). Interestingly, each of these epigenetic regulators are enzymes whose activity can be modulated by natural or synthetic inhibitors that strongly affect the differentiation potential of osteoblasts (2, 3, 6, 12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with its functional role in bone cell differentiation, Suv420h2 depletion by siRNA suppresses the maturation potential of MC3T3-E1 pre-osteoblastic cells by reducing Alp activity, ECM mineralization, as well as the expression of osteoblast-related biomarkers (e.g., Ibsp , Col1a1 or Sp7 ). Our finding that Suv420h2 is a positive regulator of osteoblast differentiation complements our previous studies that established the importance of other epigenetic regulators, including the H3K27 methyl transferase EZH2 (4, 5), DNA hydroxymethylases TET1 and TET2 (2, 3), DNA methyl-transferases (29, 30) and histone deacetylases (31). Interestingly, each of these epigenetic regulators are enzymes whose activity can be modulated by natural or synthetic inhibitors that strongly affect the differentiation potential of osteoblasts (2, 3, 6, 12).…”
Section: Discussionsupporting
confidence: 89%
“…These enzymes may function as pharmacological targets and thus present an enticing opportunity for manipulation of the biological properties of cells during cell growth and differentiation. Recently, we have shown that natural compounds can alter chromatin via active DNA demethylation (2, 3) and that drug-induced inhibition of the H3K27 methyltransferase Ezh2 significantly supports osteoblastic differentiation and bone formation in vitro and in vivo (4, 5). These studies provide proof-of-concept that the activity of epigenetic regulators (EpiRegs) can be leveraged to promote osteogenic lineage progression (6-8), and provide the rationale for investigating the roles of other EpiRegs during osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, modulating the activity of histone deacetylases (HDACs), the WD-repeat domain protein WDR5, which is associated with a histone 3 lysine 4 (H3K4) methyltransferase complex, and the H3K9 methyl transferase SUV420H2 can stimulate osteogenic differentiation of MSCs and/or pre-osteoblasts [Di Bernardo et al, 2009; Dudakovic et al, 2013; Farzaneh et al, 2016; Gordon et al, 2015; Gori et al, 2001; Gori et al, 2006; Lee et al, 2009; Schroeder and Westendorf, 2005]. Other studies have demonstrated that suppression of histone 3 lysine 27 trimethylation (H3K27me3) or altering CpG methylation can significantly enhance osteogenic differentiation and inhibit adipogenic differentiation of MSCs [Dudakovic et al, 2016; Dudakovic et al, 2015b; Hemming et al, 2014; Jing et al, 2015; Thaler et al, 2016; Wei et al, 2011]. These studies demonstrate that the epigenetic landscape is deformable to favor selective commitment of mesenchymal stromal/stem cells to the osteogenic lineage.…”
Section: Introductionmentioning
confidence: 99%
“…RANKL is a member of the tumor necrosis factor (TNF) family [11]. Binding of RANKL to RANK results in the recruitment of the TNF receptor-associated factor 6 (TRAF6).…”
Section: Introductionmentioning
confidence: 99%